T-S fuzzy BIBO stabilisation of non-linear systems under persistent perturbations using fuzzy Lyapunov functions and non-PDC control laws - Salcedo, José V.; Martínez, Miguél; García-Nieto, Sergio; Hilario, Adolfo (Zielona Góra: Uniwersytet Zielonogórski)
This paper develops an innovative approach for designing non-parallel distributed fuzzy controllers for continuous-time non-linear systems under persistent perturbations. Non-linear systems are represented using Takagi-Sugeno fuzzy models. These non-PDC controllers guarantee bounded input bounded output stabilisation in closed-loop throughout the computation of generalised inescapable ellipsoids. These controllers are computed with linear matrix inequalities using fuzzy Lyapunov functions and integral delayed Lyapunov functions. LMI conditions developed in this paper provide non-PDC controllers with a minimum *-norm (upper bound of the 1-norm) for the T-S fuzzy system under persistent perturbations.
Keywords: linear matrix inequalities; Takagi-Suegno fuzzy systems; fuzzy Lyapunov functions; integral delayed Lyapunov functions (IDLFs); non-parallel distributed fuzzy controllers (non-PDC); generalised inescapable ellipsoids